Illegal product manufacturing and exportation from Pakistan: Revealing the factuality of highly processed wildlife skin samples via DNA mini-barcoding. (4th March 2018) - Khan, Fida Muhammad; William, Kainaat; Aruge, Samreen; Janjua, Safia; Shah, Safdar Ali
ABSTRACT: Illegal trade is a major threat to the biodiversity and the efforts initiated for the conservation of wildlife. The shortcomings of the traditional taxonomic identification methods have been coped by a revolutionary and emerging technique, the "DNA (Deoxyribonucleic Acid) barcoding". Here we report a case of trader who was allegedly making footwear for a famous international celebrity from wild animal cutis. The samples confiscated during a raid on a footwear manufacturing industry by KP Wildlife department in August, 2016, were received by Bioresource Research Centre (BRC) for molecular identification on 1 st September, 2016. The study costed about USD 88 from processing to the identification of the samples. The samples identified via DNA mini-barcoding by targeting cytochrome oxidase I (COI) gene belong to Gazella bennettii and Bos taurus . Such studies are helpful for credible investigations that only lead to effective prosecution and control of illegal wildlife trade ultimately helping in conservation of wild animals.